Diskursus Al-kitab dan Al-Qur’an sebagai Wahyu Ilahi dalam Konteks Penafsiran Al Qur’an - Amiruddin; Fadhail Ramadhan, Ahmad; Kurniawan, Heri (UNIVERSITAS SERAMBI MEKKAH, 2025)
The originality of the Bible, which the Qur'an alludes to, has become an debate in believing in the books of God. Whereas both are equally a revelation from God. Likewise revelation Divine revelation, which in general is kalam or information that God gave to the Prophets and Messengers. Prophets and Messengers. However, on the one hand, Allah also gave revelation to Maryam, the mother of Prophet Isa. to Maryam the mother of the Prophet Isa, to the Mother of Moses, as well as to animals such as bees. bees. This paper aims to find the intersection of the Bible and the Quran as revelations of God through an analysis of Quranic interpretation. God's revelation through analyzing the interpretation of the Quran. Through this analysis, it can be Through this analysis, it can be concluded that the Bible and the Koran have relationships and similarities, one of which is that God is one, namely Allah. one of which is that God is one, namely Allah SWT. And that the revelation given by God to the Prophet is to give laws or sharia to humans while the revelation given to other than laws or sharia to humans while the revelation given to other than the Prophet is as inspiration or to provide instructions. Prophet is as inspiration or to provide instructions.